Answer:
The fourth option is the correct answer
Step-by-step explanation:
The given expression is
-2n(5+n-8-3n)
Given that n=3,We substitute the value of n into the expression and simplify.
This implies that,
-2n(5+n-8-3n)=-2(3)[5+3-8-3(3)]
=-6(5+3-8-9)
=-6(-9)
=54
Hence the answer is 54
Answer:16???
Step-by-step explanation:
Answer: y = 0.5x - 2
Step-by-step explanation: 0.5x = half of a number X
Answer:
A. B.
Step-by-step explanation:
Answer:
$16.25 for 1 pillow
Step-by-step explanation:
To find the cost of 1 pillow divide 65 by 4.
65/4 = 16.25